What Do You Do When Students Don’t Do the Reading? - Newton, Richard (Bulletin for the study of religion, 2022)
Sage D’Vice is back with answers, or at least responses, to readers’ questions. If you have something you want to know about working in the field or you’re just looking for a little perspective, send your question to our editorial team. We’ll make sure to make it anonymous. In this installment of The Question, a seasoned teacher is weary of students coming to class having not read. Sage D’Vice can relate and has some thoughts on how to handle this evergreen predicament.